Safe amine based zinc dithiocarbamates for the vulcanization of carbon black reinforced natural rubber. Issue 6 (6th October 2013) - Alam, Md. Najib; Mandal, Swapan Kumar; Roy, Kumarjyoti; Debnath, Subhas Chandra
ABSTRACT Binary combination of three safe amine based synthesized zinc dithiocarbamates (ZDC), namely zinc (N‐benzyl piperazino) dithiocarbamate (ZBPDC), zinc (N‐ethyl piperazino) dithiocarbamate (ZEPDC), and zinc (N‐phenyl piperazino) dithiocarbamate (ZPPDC) with mercapto benzothiazole disulfide (MBTS) as an effective accelerator system for the vulcanization of carbon black (N330, N550, and N774) filled natural rubber (NR) composites are studied. A comparison between the safe amine based zinc dithiocarbamates with the unsafe zinc dimethyl dithiocarbamate (ZDMC) in the light of mechanical and aging resistance behavior, introduces the non carcinogenic rubber additives in the filled vulcanization of rubber. Both accelerator and filler have the major importance for improving the mechanical as well as aging resistance behavior of the resultant vulcanizate. Variation in the filler and also filler to oil ratio are done to optimize the mechanical properties. SEM studies of different types of filler with different amounts show that N330 at 30 phr loading composites forms more homogeneity and less aggregated structures. Natural rubber systems with N330 carbon black show the best results with respect to tensile strength, but after the aging N774 carbon black filled system indicates better retention in the tensile strength. ZPPDC‐MBTS accelerated vulcanizate shows the better age resistance behavior than ZDMC‐MBTS accelerated vulcanizate. From both the points of age resistance and mechanical properties, ZBPDC‐MBTS accelerator system is the suitable substitute for ZDMC‐MBTS accelerated system in the filled vulcanization of natural rubber composites. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2014, 131, 39988.